Harmonizing Sharia Accounting and Corporate Culture: A Pathway to Better Decision-Making - Syah, Arzal; Jafar, Erwin; Nurpratiwi, Dini; Jasnur, Avrilia; Ar Rasyid, Aidil; Imam, Abdi (JIFA (Journal of Islamic Finance and Accounting), 2024)
This study explores the relationship between cognitive bias, heuristic bias, and corporate culture in the context of sharia accounting decision making in Indonesia. The results show that cognitive bias does not have a significant effect on decision making, while corporate culture is proven to moderate the effect of cognitive bias on sharia accounting decisions. On the other hand, heuristic bias also has no direct effect, and the interaction between corporate culture and heuristic bias does not show a significant impact. These findings emphasize the importance of corporate culture in forming a framework that can reduce the negative impact of cognitive bias in decision making. The practical implications of this study suggest that companies need to integrate sharia values ​​into their organizational culture to improve the quality of decision making, thereby creating a more transparent and accountable environment. Theoretically, this study contributes to the understanding of how psychological and cultural factors can influence each other in the context of sharia accounting, paving the way for further research that can deepen the analysis of the integration of sharia values ​​in business practices.